Antecedents of Technological Diversification: A Resource Dependence Logic - Xuanjin Chen (Journal of Open Innovation: Technology, Market and Complexity, 2019)
This paper extends resource dependence logic by investigating the antecedents of technological diversification and further identifies its boundary condition. We argue that this resource dependence logic is bound by state ownership through coalitions with firms, a less discussed component of interdependence. The empirical results, based on a panel data analysis of Chinese listed firms, suggest that environmental dynamism positively relates to technological diversification, while environmental munificence negatively relates to technological diversification. These relationships changed when state ownership is considered. The theoretical implications for resource dependence theory and diversification research are discussed.